THE BENEFITS OF VIRTUAL REALITY ON PAIN, ANXIETY AND EARLY REHABILITATION IN PATIENTS IN THE INTENSIVE CARE UNIT (REMUNOM, 2025)
Objective: In the available productions, the benefits that virtual reality (VR) presents to patients admitted to the intensive care unit (UCI). Methodology: The present study was a systematic review of a qualitative nature. Results: From the 8 articles selected for the study of this publication it was possible to analyze that virtual reality, despite being a recent technology, stood out as a promising tool in the rehabilitation of critically ill patients. In this context, the biases highlighted in the present articles show how VR works in the intensive care environment with a focus on analgesia, improving the psychosocial state and gaining or preserving patients' mobility. The articles researched also showed that virtual reality is well tolerated by patients. Conclusion: Innovative technologies such as virtual reality enhance the emergence of new types of therapy in intensive medicine, improving pain, discomfort, psychological changes and early rehabilitation, thus promoting benefits that can improve patients' quality of life. However, new studies are necessary to maximize the subject